DEVELOPMENT OF INTERACTIVE ALGEBRA LEARNING VIDEOS TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ LEARNING OUTCOMES - Restu, Melisa; Nurdiana, Aty; Rahmawati, Fitriana (CV. Doki Course and Training, 2025)
This study aims to develop an interactive learning video for algebra materials and to examine its feasibility, practicality, attractiveness, and effectiveness in improving students’ learning outcomes at SMP Taman Siswa Teluk Betung, Bandar Lampung. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through questionnaires, test, and documentation. Quantitative data were analyzed using Likert-scale percentage analysis, while qualitative data in the form of expert feedback were used to revise the developed product. The validation results indicated that the learning video was valid in terms of content, with an average score of 4.6, very valid in media aspects with a score of 4.5, and valid in language aspects with a score of 4.45. The implementation results showed that teachers rated the video as very practical with a score of 4.9, students perceived it as attractive with a score of 4.0, and student learning mastery reached 81.48%, exceeding the minimum mastery criterion. These findings indicate that interactive learning videos are feasible and effective as instructional media to enhance students’ understanding of algebra concepts and improve learning outcomes in junior high school mathematics.